Aspectos fotoquímicos y actividad cicatrizante de Senecio Culcitoides Weed - Soriano S., Marcela Y. (2004)
The vegetable species in study were located and gathered in the month of February in the town of Ticlio located between 4500 to 5000 o.s.l. to the height of the km 130 of the central highway, in the area of mountain of the department of Lima. It was classified in the Museum of Natural History as: Senecio culcitoides Weed. of vulgar name:, Huajchor, Semaro Huamasti, According to Jaroroslav Soukup (1). For the extraction of the secondary metabolites was realized a maceration etanólica of lea ves of Se necio culcitoides Weed being continued solubility test and the screening respective fitoquímico, being bigger quantity of phenolic compound , as flavonoides, tannins, etc., besides alkaloids, steroids and/or triterpenoides. The structural elucidaban by means of ultraviolet espectroscopía - visible, was determined that they belonged to phenolic compound derived flavonoides belong the nucleus: flavanonona (5,7 dihidroxi-4',6,8-trimetoxiflavanonona; 3',5-dihidroxi- 4'-metoxi-7-or-rhannoglucosyl flavanonona) and a chalcona (3,4,-dihidroxichalcona).The evaluation of the healing activity of the extract at 20% in form of crea m was according to the tensiométrico method, statistically, it was observed that the resistance levels to the tension of the etanólic extract of the Senecio culcitoides Weed presented a significant difference of P <0.05 being compared with the control that it was a cream base cetiol lanette 6% and with the standard one the fármaco Vibe (sangre de grado 1%), those results were corrobarated with the respective histolagy.